INFORMATION GAP ACTIVITIES TO IMPROVE STUDENTS’ ORAL PROFICIENCY AT PKBM CANDRA KIRANA - Muhamad Maulidi; Mohammad Amiruddin (Universitas Madura, 2021)
This study is about the suggested activities which are Information Gap Activities intended to qualify the students’ oral proficiency. The writer chooses this topic since there is most of the students’ lack of the activities which can motivate students to develop their communicative proficiency. Almost of the classroom activities only consist of statement of grammar rules, list of vocabularies, and sentences for translation. While oral practice was limited to students. Because of that the writer tries to provide Information Gap Activities which can motivate the students of Pusat Kegiatan Belajar Masyarakat (PKBM) Candra Kirana. In this study, the writer uses the first-year student of PKBM Candra Kirana as the subject of the study. The writer designs the lesson plans, implementing the actions, making observations and reflecting on the results. This study was conducted in three cycles. To collect data, the writer used instruments of observations, lists, tests, and questionnaires. The data obtained was presented in two ways, qualitatively and quantitatively. The findings showed that IGT activities were effective in improving the students’ oral proficiency. This can be seen from the improvements after each cycle. This can be seen by the rise of students’ mean scores in the test results: 58.7 in the first cycle, 67 in the second cycle and 83.3 in the third cycle. Improvement was also seen based on the results from the observations that showed positivity, and good responses from the students from the questionnaire results. This means that the students responded positively to the implementation of this technique.